Effects of Different LEDs Light Combination on the Proliferation, Rooting and Growth of Two Kinds of Ornamental Dendrobium Tissue Culture Seedlings - Yao WU; Zaihua WANG; Guangying YE; Yi YANG; Houcheng LIU; Rong ZHOU (Guangdong nongye kexue)
【Objective】The study aims to screen the high-quality LEDs combination suitable for the proliferation, rooting and shoot strengthening of ornamental Dendrobium clonal seedlings, with a view to providing a basis for seedling quality improvement and standardized production.【Method】We studied the effects of 8 different light combinations including LEDs (red, blue and green) and white light (W) on the proliferation, rooting, shoot strengthening and growth of tissue culture seedlings of 2 popular Dendrobium varieties, Dendrobium Mini Red and Dendrobium Angel Baby 'Love Pocket'.【Result】D. Mini Red had the best proliferation effect in light quality culture of R6B3G0, the proliferation coefficient reached 2.35 per plant, and its fresh weight, dry weight and dry matter content were 3.941 g/plant, 0.2731 g/plant and 7.06%, respectively; the root number and average root length were 14.20 roots/plant and 2.81cm, respectively. The proliferation of D. Angel Baby 'Love Pocket' was the best in light quality culture of R6B3G0, the proliferation coefficient was 3.11 per plant, and the fresh weight, dry weight and dry matter content were 0.258 g/plant, 0.0218 g/plant and 8.58%, respectively; the best root effect was obtained under the light quality treatment of R6B3G0, and the root number and average root length were 10.98 roots/plant and 3.00 cm, respectively. Finally, PCA principal component analysis was used to classify the rooting seedlings of the above two Dendrobium varieties, and it was concluded that the first-class seedlings of D. Mini Red were the most in light quality culture of R3B3G3, R3B6G1 and R3B6G3 (46.7%-53.3%), and the survival rate of domesticated seedlings reached 100%; however, the first-class seedlings of D. Angel Baby 'Love Pocket' were the most in light quality culture of R6B3G0 (53.3%), and the survival rate of domesticated seedlings reached 100%.【Conclusion】Appropriate combination of red, blue and green LED light quality can promote the tissue culture and growth of clonal seedlings of D. Mini Red and D. Angel Baby 'Love Pocket', and cultivate more high-quality first-class seedlings. The results of this study provide technical reference for the application of LED light source in tissue culture production of ornamental Dendrobium and the standardized production of high-quality seedlings.